MODAL SOSIAL PENYULUH: PERAN KEPERCAYAAN DALAM KEGIATAN PENYULUHAN PERTANIAN DI KOTA KENDARI - Niya, Wa Ode Nur; Taufik, Yani; Salahuddin, Salahuddin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
The objective of this study was to ascertain the extent of social capital among extension workers in Kendari City, with a particular focus on the role of trust in the implementation of effective agricultural extension activities. The study population consisted of all agricultural extension workers in Kendari City, numbering 63 individuals. The research sample was selected using the census technique, which involves taking the entire population, resulting in a sample size of 63 respondents. The data were collected via survey, interview, and document analysis techniques, employing a variety of media formats, including questionnaires. The research variables concentrated on the social capital of extension workers, specifically in the context of trust in agricultural extension activities. This research employs a quantitative methodology. The data were analyzed using a quantitative descriptive approach. This method employs mathematical and statistical calculations for testing, measurement, and hypothesis testing. The findings indicated that the social capital of the extension workers in Kendari City, specifically their trust in agricultural extension activities, has been effectively implemented. Trust in agricultural extension activities is a crucial element in the success of extension work. The relationship between extension workers and farmers plays a pivotal role in this process. By fostering effective communication and mutual respect, trust can be established, which in turn will encourage the adoption of more effective and sustainable agricultural practices.